Cultural techniques for high quality and high benefits of 'Jiefangzhong' cultivar - Chen T. (First international symposium on loquat, 2003)
'Jiefangzhong' is the leading cultivar in Changtai town, it accounts for more than 85 percent of the total area (4000 ha). The present paper outlines the cultivar practices needed for obtaining high quality fruits with efficiency. They are based on observations during many years of loquart culture in the area. These practices have been recommended to loquat growers for more than 15 years.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)